(untitled) (Journal Nutrizione, 2025)
The level of compliance with healthy eating patterns in Indonesia is still low even though various campaigns have been carried out, such as the Healthy Living Community Movement (GERMAS). Low nutritional literacy, lack of motivation, and social and cultural influences are the main factors that hinder changes in people’s consumption behavior. In this context, mobile applications emerge as a potential solution with interactive features such as food tracking, notifications, and visual education that are personalized and easily accessible. Previous studies have shown that approaches based on behavior change theories, such as Self-Determination Theory and Theory of Planned Behavior, increase the effectiveness of digital interventions in forming healthy eating habits. This study uses a literature review method with a qualitative approach to examine the effectiveness of mobile applications in increasing compliance with healthy eating patterns. Data sources were obtained from national and international journals in the last ten years (2015–2025), which were analyzed using thematic analysis techniques. The results of the study show that the success of the application depends not only on technological features, but also on user-need-based interface design, integration of behavioral theories, and social and professional support. Therefore, digital nutrition applications need to be developed in a multidisciplinary manner to create an inclusive and sustainable impact in community nutrition interventions